State of the Art: Big Data and Business Intelligence (2019)
Managers must improve their knowledge of data resources and how to use them in their companies, especially in PYMES (small and medium-sized companies). In many companies, managers believe that data-driven solutions are only for managers in large companies because the cost is very expensive. In some companies, the information systems are antiquated and in others it has not been politically acceptable to save the data generated. These are problems in companies, especially in developing parts of the World. For example, in Colombia managers are still developing data-driven cultures and developing information systems that can help their firms compete with other companies in other markets. This article presents the state of the art of Big Data and Business Intelligence based upon presentations made at a September 2016 congress held at the Cahtolic University of Pereira